Penerapan Strategi Marketing Digital dan Peran Sistem Informasi Manajemen dalam Pelayanan Administrasi Kependudukan di Kelurahan Petemon - Ananda Leony; Siti Ning Farida (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
In the current era of the industrial revolution, Indonesia has also developed information technology which has an important and fundamental role, both for society and the government. This study discusses the application of digital marketing strategies and the role of management information systems in population administration services in Petemanon Village. Living in an all-digital way encourages the Surabaya City Population and Civil Registration Office to present innovations in the use of information technology in the form of web-based public service information systems. The innovation of a website-based public service information system offers many conveniences supported by the implementation of digital marketing strategies through Instagram. The research method used is descriptive research whose data is obtained from observation and documentation. Based on the results of the discussion, it was found that the implementation of digital marketing strategies and management information systems has an important role in assisting the implementation of population administration registration.